Insect as Biological Indicator from Protected to The Disturb Landscape in Central Java Indonesia - Wicaksono, Karuniawan Puji; Suryanto, Agus; Nugroho, Agung; Nakagoshi, Nobukazu; Kurniawan, Nia (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
In the biological science, invertebrate (especially insect) diversity is relatively well known. Yet, little study about their interaction with specific land use or specific system function. With the rapid changes of landscape, biodiversity is also changes in response to human impact; due to each organism have the specific interaction with certain environment. In this research, the assessment of insect order in the different landscape types was conducted using several method of trapping to understand the specific pattern of insect which are inhabited the landscape. The objectives of this research were monitored the Insect diversity, its ecological importance to agro-forestry ecosystem, and compare it with other forest type in this area. Another objective was determined the insect characteristic as the indicator of environmental quality on each land-use system (forest, agroforestry, plantation and monoculture). Monoculture agriculture has the largest number of Lepidoptera and Hemiptera order (herbivore insect dominated) while in agro-forest system has the largest number of Diptera and coleoptera order. Protected forest, plantation forest and agro-forestry showed the similar index number which shows the similar ecological services for the insect as their habitat. However, in the monoculture agriculture, there was an unbalance insect composition and high dominance.Keywords: landscape, biodiversity, environment indicator index